Morphometry of the reproductive system of the predator Podisus nigrispinus (Dallas, 1851) (Hemiptera, Pentatomidae) when submitted to different temperatures - Santos,Ítala Tainy Barreto Francisco dos (2020)
ABSTRACT: In order to manipulate the mass rearing of natural enemies, temperature variations can be used. The effects are widely studied for their survival and developmental duration; however, there is little information about their reproductive system in the literature. Therefore, the purpose of this study was to evaluate the effects of different temperatures on the reproductive system of the predator Podisus nigrispinus (Dallas, 1851) (Hemiptera: Pentatomidae). The predator was kept at temperature conditions of 17, 21, 25, and 29 °C until reaching 15 days of age, the adult stage. The insects were then killed, measured for both weight and size, dissected, and then evaluated for the following parameters: length of the most developed ovariole; number of ovarioles per ovary; number of oocytes per the more developed ovarioles; number of oocytes per P. nigrispinus female; and the total area of the testicles was measured in the male insects. Results showed that as the temperature increased, the parameters were positively affected. These temperature variations can be used to manipulate the mass rearing of P. nigrispinus under controlled conditions.